2001
DOI: 10.1034/j.1399-3054.2001.1110308.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of antioxidative enzymes to plum pox virus in two apricot cultivars

Abstract: Recent evidence has indicated that activated oxygen species (AOS) may function as molecular signals in the induction of defence genes. In the present work, the response of antioxidative enzymes to the plum pox virus (PPV) was examined in two apricot (Prunus armeniaca L.) cultivars, which behaved differently against PPV infection. In the inoculated resistant cultivar (Goldrich), a decrease in catalase (CAT) as well as an increase in total superoxide dismutase (SOD) and dehydroascorbate reductase (DHAR) activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 79 publications
6
46
0
1
Order By: Relevance
“…In these cells, that are not able to trigger a response to stop pathogens, the APX increase limits the propagation of oxidative processes allowing cells to maintain their viability, a condition required for the penetration of biotrophic powdery mildew in plant tissues (Burhenne and Gregersen, 2000). This up-regulation of APX confirms previous results reporting an increase in APX activity during successful infection of barley leaves by biotrophic compatible pathogens (El-Zahaby et al, 1995;Vanacker et al, 1998;Kuzniak and Sklodowska, 1999) and has also been reported to occur in leaves of susceptible apricot infected by Plum pox virus (Hernandez et al, 2001). …”
Section: Ascorbate Peroxidase (Apx)supporting
confidence: 80%
“…In these cells, that are not able to trigger a response to stop pathogens, the APX increase limits the propagation of oxidative processes allowing cells to maintain their viability, a condition required for the penetration of biotrophic powdery mildew in plant tissues (Burhenne and Gregersen, 2000). This up-regulation of APX confirms previous results reporting an increase in APX activity during successful infection of barley leaves by biotrophic compatible pathogens (El-Zahaby et al, 1995;Vanacker et al, 1998;Kuzniak and Sklodowska, 1999) and has also been reported to occur in leaves of susceptible apricot infected by Plum pox virus (Hernandez et al, 2001). …”
Section: Ascorbate Peroxidase (Apx)supporting
confidence: 80%
“…Likewise, it is known that the above-described elicitors are capable of inducing the synthesis of activated oxygen species (AOS) in the apoplast of plant cells and also modulate the level of cellular antioxidants as well as the levels of apoplastic antioxidant enzymes (Luwe, 1996;Ranieri et al, 1996;Blinda et al, 1997;Thordal-Christensen et al, 1997;Schraudner et al, 1998;Vanacker et al, 1998aVanacker et al, , 1998bPiqueras et al, 1999;Hernández et al, 2001). However, little is known about the capacity of salt to induce the synthesis of AOS in the apoplast and, in this case, the role played by apoplastic antioxidants.…”
mentioning
confidence: 99%
“…Enhanced APX activity has been found also in virus-infected plants (e. g. citrus tristeza virus in Mexican lime; Pérez-Clemente et al, 2015). Interestingly, APX activity was induced by PPV infection only in a susceptible (contrary to a resistant) apricot cultivar (Hernández et al, 2001).…”
Section: Resultsmentioning
confidence: 94%